2021
DOI: 10.1111/jrh.12598
|View full text |Cite
|
Sign up to set email alerts
|

The effect of broadband access on electronic patient engagement activities: Assessment of urban‐rural differences

Abstract: Objectives Lack of access to high‐speed internet may explain disparities in the use of technologies that support electronic patient engagement (EPE). This study describes trends in how people with and without fixed broadband connectivity in urban and rural communities used EPE tools to interact with health care providers between 2014 and 2018. Methods We linked Federal Communications Commission fixed broadband data with the Association of American Medical Colleges Consumer Survey of Health Care Access data for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Namely, telemedicine does not replace an on-site physician, some fear it may disincentivize commuting specialists, and rural patients face limitations in accessing telemedicine, such as limited internet access. 1 , 9 , 10 Unexpectedly, our data suggested telemedicine could potentially improve rural provider recruitment and retention by reducing feelings of professional isolation. This is interesting given a previous study also found telemedicine to improve recruitment and retention, specifically among hospitals using telemedicine in the ED.…”
Section: Discussionmentioning
confidence: 73%
“…Namely, telemedicine does not replace an on-site physician, some fear it may disincentivize commuting specialists, and rural patients face limitations in accessing telemedicine, such as limited internet access. 1 , 9 , 10 Unexpectedly, our data suggested telemedicine could potentially improve rural provider recruitment and retention by reducing feelings of professional isolation. This is interesting given a previous study also found telemedicine to improve recruitment and retention, specifically among hospitals using telemedicine in the ED.…”
Section: Discussionmentioning
confidence: 73%
“…Direct physician to patient telehealth services also gradually increased, [33] but were massively accelerated by the disruptive nature of the COVID-19 pandemic, with some practices shifting entirely to telemedicine [34,35]. However, pre-existing structural barriers in broadband internet access that predated the COVID-19 pandemic [36][37][38] limited the adoption of video telemedicine among all groups equally [39][40][41]. The same risks may apply with diffusion of technologic innovations within gastroenterology, where newer, highly specialized procedures may not be offered in all regions, leading patients either not to have access to the technologies locally, requiring either forgoing the treatment or long travel to subspecialty centers.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to telehealth implementation are largely centered around infrastructure, technology, and reimbursement. The infrastructure required for broadband internet needs to be improved, especially in rural America where having adequate medical infrastructure is lacking because of a “medical desert.” 89 Approximately one-quarter of American adults do not have broadband access. 90 This issue could be improved through changes in public policy to supplement efforts by the private sector.…”
Section: Strategies To Overcome Telehealth Obstaclesmentioning
confidence: 99%